IMPLIKASI TERBITNYA REGULASI TENTANG PERTIMAHAN TERHADAP HUBUNGAN ANTARA BOS DAN ANAK BUAH (SEBUAH EGALITARINAISME LOKAL) - Citra Asmara Indra, , S.Sos., M.A (Universitas Bangka Belitung, 2013)
Regulatory changes on tin by the central government or the entrance slit for local governments to take over the management of tin strengthened by the release of law on regional autonomy. Government then uses its authority to issue a local regulation that allows the general public to mine tin unconventional. Unconventional means parties other than the two mining companies, namely PT. Timah Tbk. and PT. Koba Tin has monopolized the management of lead since the Dutch colonial era, and those who become partners of both companies. Law is a legal umbrella for the people from different walks to mine tin massively without any consequences to reclaim their land dug. The implications of rising regulation of the dynamics of tin tin mining in Bangka Belitung province, particularly in Lampur village, Central Bangka regency, then look at the pattern of the relationship between the boss and the tin men in connection with the issuance of these regulations on the lives of the miners.Keyword: Regulation, Minners, and Egalitarism